Performance evaluation of rotor shears machine with bottom sieves for comminution of waste PCB - Radon Dhelika; Daniel Meino Soedira (Journal of Engineering and Applied Science)
Abstract The rapid expansion of the electrical and electronic equipment sector has led to an alarming increase in Waste Electrical and Electronic Equipment (WEEE), particularly waste printed circuit boards (PCBs), which pose significant environmental and health risks due to their hazardous metal content. This study focuses on the development and performance evaluation of a common rotor shears machine equipped with bottom sieves for the comminution of waste PCBs, aiming to enhance the efficiency of metal recovery from WEEE. Utilizing a low-speed, high-torque rotor shears design, the research investigates the impact of operational parameters, specifically sieve sizes (4 mm, 6 mm, and 8 mm) and motor speeds (700 rpm, 850 rpm, 1000 rpm, and 1150 rpm), on the machine’s performance in terms of particle size distribution, material liberation, and machine throughput. The findings reveal that higher motor speeds result in smaller particle sizes, while smaller sieve sizes contribute to a higher degree of material liberation, crucial for subsequent metal recovery processes. The best material liberation, exceeding 90%, was achieved using a 4-mm sieve at 1150 rpm. Machine throughput varied with sieve size, with the 8-mm sieve achieving the highest rate of 24 kg/h, followed by 17 kg/h for the 6-mm sieve and 10 kg/h for the 4-mm sieve. This research underscores the importance of optimizing shearing parameters to address the growing problem of WEEE and improve the efficiency of recycling processes, thereby contributing to resource conservation and mitigating the environmental and health impacts of WEEE mismanagement.